Membangun Pondasi Sekolah Adiwiyata Melalui Edukasi Lingkungan di Ponpes Mu’alimin Muhammadiyah Boarding School Narmada Lombok Barat - Adiansyah, Joni; Nurhayati, Nurhayati; Ibrahim, Ibrahim; Sukuryadi, Sukuryadi; Johari, Harry; Ghazali, Mursal (Universitas Mataram, 2025)
This community engagement program aimed to lay the foundations for the Indonesian “Sekolah Adiwiyata” (Eco‑School) model at Mu’alimin Muhammadiyah Boarding School (MBS) Narmada, West Lombok. Responding to uneven teacher understanding of environmental education, we designed a short, participatory capacity‑building intervention that combined an interactive presentation, guided discussion, and a rapid pre–post assessment. The activity was conducted on 20 September 2025 with 18 participants—boarding school leaders, the principal, and teachers. Content focused on (a) Adiwiyata concepts, goals, and benefits; (b) eligibility requirements; and (c) practical preparation strategies including establishing an Adiwiyata Team, drafting a one‑year School Environmental Work Plan (RKLS), integrating environmental values into lesson plans (RPP), and documenting evidence. Baseline insights indicated that more than half of the teachers did not yet understand the Adiwiyata concept. Following the session, all participants reported understanding the concept and were able to articulate its four core components (policy, curriculum, participatory activities, and eco‑friendly facilities). Discussion emphasized cultural relevance by linking ecological stewardship to Islamic values, which helped reframe Adiwiyata as a moral mission rather than mere compliance. The program also generated an agreed roadmap for curricular alignment and initial school‑wide practices (waste segregation and simple composting). We conclude that a targeted, context‑sensitive workshop can rapidly improve foundational knowledge and unlock organizational readiness for Eco‑School transformation, provided it is followed by structured mentoring and systematic documentation.